Posted by **Jennifer** on Sunday, January 18, 2009 at 6:24pm.

3-6(t-7)= 8-5(2t+1)

7x+26-5x = 5x-2+x

I am not sure how to start these.

Any help?

- Intermediate Algebra Solve -
**PsyDAG**, Sunday, January 18, 2009 at 6:50pm
Get rid of parentheses and combine like terms.

3 - 6(t-7) = 8 - 5(2t+1)

3 - 6t + 42 = 8 - 10t -5

42 = -4t

You should be able to continue from here and do the same process with the second equation.

I hope this helps. Thanks for asking.

- Intermediate Algebra Solve -
**Damon**, Sunday, January 18, 2009 at 7:02pm
multiply out parentheses first

3 - 6 t + 42 = 8 - 10 t - 5

combine like terms on left and on right

45 - 6 t = 3 - 10 t

add 10 t to both sides

45 + 4 t = 3

subtract 45 from both sides

4 t = - 42

divide both sides by 4

t = - 10.5

--------------------

check

3 - 6 (-10.5-7) = 8 - 5 (2*-10.5 + 1) ????

3 + 63 + 42 = 8 +105 - 5 ???

108 = 108 check Caramba !

## Answer this Question

## Related Questions

- intermediate algebra - solve each equation and check the result 7 3 40 x-5 - x+5...
- Intermediate Algebra - Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x...
- Intermediate Algebra Solve - Solve: -1/3 - 5/4t = 3/4 - 1/6t would I cross ...
- Calculus - I finished the first question with no problem. It was something like...
- Intermediate Algebra - solve for q: 1 = 1+ 1 __ __ __ f p q
- intermediate algebra - Solve....x(x-3)=x-9
- Intermediate Algebra - Solve....x(x-3)=x-9
- Intermediate Algebra - Solve for X (1/8)=(2/3)x-1/2
- Intermediate Algebra - Solve 6x=5-9 6x=-4 x=-2/3
- intermediate algebra - solve: 3/4x + 2/5 - x =3/10